A Review on Natural Plant Based Polymers: A Brilliant Pharmaceutical Excipients (International Journal of Food and Nutritional Sciences, 2022)
There are various synthetic and semi synthetic polymers are available in market for pharmaceutical formulation, but these polymers have certain disadvantages such as side effects, high cost, toxicity, poor patient compliance, environmental pollution during synthesis and non-renewable sources. Because of these disadvantages they are avoid to use in pharmaceutical preparation and are replaced by some plant based excipients such as natural gums and mucilage are preferred to semi synthetic and synthetic excipients. A large number of natural plant based pharmaceutical excipients are available today. Gums and mucilages are one of them and most commonly available plant ingredients with a wide range of applications and advantages like easily available in nature, cheap, safe, economy benefit and biocompatible. They have been extensively explored as pharmaceutical excipients because of natural ingredients, chemically inert, nontoxic, less expensive, biodegradable and widely available. Recent trend toward the use of plant based and natural products demands the replacement of synthetic additives with natural ones. In this review, we describe the pharmaceutical applications of various natural gums, mucilages and their modified forms for the development of various drug delivery systems.